High-strength heat-resistant silicone rubber composite material, preparation method thereof and electric power fitting spacer rod
Patent Information
- Application Number
- CN202611192123.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-13
AI Technical Summary
然而,现有技术存在填料分散不均、耐热剂分布不均、交联反应控制困难等问题,填料分散不均会使硅橡胶材料在受到高温老化时界面脱粘,无法承受机械应力和疲劳载荷;耐热剂分布不均则会导致硅橡胶材料的耐热性能分布不均;交联反应控制困难会导致最终形成的硅橡胶材料内部的交联网络结构均匀性不足,无法提供优异的力学强度
[0052]本申请实施例提供的高强度耐热硅橡胶复合材料及其制备方法、电力金具间隔棒,通过将硅烷改性氧化硅与耐热助剂进行预先混合分散,并结合负载型铂催化剂、惰性气氛条件下的预交联及包含若干次升降温循环的二次交联反应,能够提高填料和耐热助剂在硅橡胶体系中的分散均匀性及其与基体的界面稳定性,同时改善交联反应的可控性和交联网络的均匀程度,进而减轻材料内部应力集中,提升复合材料的力学性能、耐热性能及耐热老化稳定性。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the field of silicone rubber materials, and in particular to a high-strength heat-resistant silicone rubber composite material and its preparation method, and a spacer bar for power fittings. Background Technology
[0002] In high-voltage transmission lines, power fitting spacers, as conductor spacing fixing devices, must withstand the dual effects of high-frequency mechanical vibrations caused by conductor galloping and current-carrying temperature rises (up to 150℃ or higher) over long periods. They must also withstand ultraviolet radiation, humid and hot climates, and long-term thermal aging in outdoor environments. Furthermore, seals or stress cones in high-voltage cable accessories (such as cable terminations and intermediate joints) must maintain long-term sealing performance and uniform electric field distribution at cable operating temperatures (typically 90℃-120℃), while resisting material performance degradation due to thermal cycling. These application scenarios place stringent requirements on the comprehensive performance of silicone rubber materials, the component used in power fitting spacers or high-voltage cable accessories: on the one hand, they must possess excellent mechanical properties (such as high tensile strength, tear strength, and elastic modulus) to withstand mechanical stress and fatigue loads; on the other hand, they must possess excellent high-temperature aging resistance (such as tensile strength retention ≥80% after 72 hours at 300℃) to ensure that the material does not crack, pulverize, or significantly degrade in performance during long-term service.
[0003] In existing technologies, the preparation of heat-resistant silicone rubber materials typically uses vinyl silicone oil or methyl vinyl silicone rubber as the base rubber, adding inorganic fillers such as quartz powder and fumed silica as reinforcing agents, and combining them with heat-resistant additives (such as phenyl silicone oil, cerium oxide, or polymetallic organosiloxanes) to improve high-temperature stability. Hydrogen-containing silicone oil is used as a crosslinking agent, and a hydrosilylation reaction is initiated by a noble metal catalyst such as chloroplatinic acid. The final product is prepared through a single mixing or internal mixing molding process. However, existing technologies suffer from problems such as uneven filler dispersion, uneven distribution of heat-resistant agents, and difficulty in controlling the crosslinking reaction. Uneven filler dispersion can cause the silicone rubber material to debond at the interface during high-temperature aging, making it unable to withstand mechanical stress and fatigue loads. Uneven distribution of heat-resistant agents leads to uneven distribution of the heat resistance properties of the silicone rubber material. Difficulty in controlling the crosslinking reaction results in insufficient uniformity of the crosslinked network structure within the final silicone rubber material, failing to provide excellent mechanical strength.
[0004] For example, Chinese patent CN104046039A discloses a heat-resistant silicone rubber and its preparation method. In the disclosed preparation method, polymetallic organosiloxane is added as a heat-resistant additive in the form of solid powder. The particle size is relatively large and the bonding mode with the matrix is simple, which limits the uniformity of the distribution of the heat-resistant agent in the matrix. In the one-time internal mixing molding process, the crosslinking reaction is concentrated. The catalyst used for the hydrosilylation reaction is directly added, which leads to an excessively fast reaction rate. The concentrated exothermic crosslinking reaction causes uneven crosslinking density, and stress concentration is easily generated inside the silicone rubber material. The traditional one-time molding process is difficult to build a uniform and stable crosslinking network structure. The silicone rubber material produced cannot simultaneously meet the dual requirements of high strength and high temperature aging resistance required for power fitting spacers.
[0005] Therefore, there is an urgent need to provide a silicone rubber composite material to achieve a synergistic improvement in mechanical properties and heat resistance, so as to meet the stringent requirements of high-end application fields such as power fitting spacers and high-voltage cable accessories. Summary of the Invention
[0006] This application provides a high-strength heat-resistant silicone rubber composite material and its preparation method, as well as an electrical fitting spacer, so that the obtained silicone rubber composite material can maintain heat resistance while taking into account high mechanical strength and heat aging resistance.
[0007] In a first aspect, embodiments of this application provide a method for preparing a high-strength heat-resistant silicone rubber composite material, comprising: mixing silane-modified silica with a heat-resistant additive and dispersing it in an organic solvent to obtain a filler premixed slurry;
[0008] Platinum catalysts are supported on a support to obtain slow-release catalysts;
[0009] After mixing vinyl silicone oil with the filler premix slurry, the slow-release catalyst is added, and hydrogen-containing silicone oil is added under an inert atmosphere to carry out a pre-crosslinking reaction and a secondary crosslinking reaction to obtain a rubber compound; wherein, the secondary crosslinking reaction includes several heating and cooling cycles;
[0010] The rubber compound is post-processed to obtain the high-strength heat-resistant silicone rubber composite material.
[0011] In one possible implementation, the silane-modified silicon oxide is prepared by a method comprising the following steps:
[0012] Silica and silane coupling agent are mixed at a mass ratio of 100:(1-3) and stirred at 50℃-60℃ for 10min-20min to obtain the silane-modified silica.
[0013] And / or, the mixing and dispersion of silane-modified silica with a heat-resistant additive in an organic solvent includes:
[0014] The silane-modified silica and the heat-resistant additive are mixed at a mass ratio of 100:(5-10), stirred at 70℃-80℃ for 15min-30min, and then an organic solvent is added and ultrasonically dispersed for 10min-30min to obtain the filler premix slurry.
[0015] In one possible implementation, the silane coupling agent comprises at least one of γ-methacryloxypropyltrimethoxysilane, γ-glycidyl etheroxypropyltrimethoxysilane, and γ-aminopropyltriethoxysilane.
[0016] And / or, the heat-resistant additive includes at least one of cerium oxide, titanium oxide, and cerium hydroxide;
[0017] And / or, the organic solvent includes at least one of anhydrous isopropanol and n-butanol;
[0018] And / or, the mass ratio of the silicon dioxide to the organic solvent is 10:(5-8).
[0019] In one possible implementation, the carrier includes a first carrier and a second carrier, wherein the pore size of the first carrier is greater than or equal to the pore size of the second carrier;
[0020] The slow-release catalyst includes a first slow-release catalyst and a second slow-release catalyst.
[0021] In one possible implementation, the loading of the platinum catalyst onto the support includes:
[0022] The platinum catalyst was dispersed in an alcohol solvent to obtain a platinum catalyst dispersion.
[0023] According to the mass ratio of the platinum catalyst to the first support being (1-5):100, the first support is added to the platinum catalyst dispersion and impregnated for 12h-24h, with regular stirring during the period, and then filtered and dried to obtain the first slow-release catalyst.
[0024] The second support was added to the platinum catalyst dispersion at a mass ratio of (1-5):100, and impregnated for 12-24 hours with periodic stirring. The mixture was then filtered and dried to obtain the second slow-release catalyst.
[0025] In one possible implementation, the pore size of the first carrier is 2nm-10nm;
[0026] And / or, the pore size of the second carrier is 2nm-5nm;
[0027] And / or, the mass ratio of the first sustained-release catalyst to the second sustained-release catalyst is (4-6):(4-6).
[0028] In one possible implementation, the platinum catalyst comprises at least one of chloroplatinic acid, platinum-divinyltetramethyldisiloxane complex, and platinum-cyclohexene complex;
[0029] And / or, the first carrier includes at least one of mesoporous silica and molecular sieve;
[0030] And / or, the second carrier includes at least one of activated carbon and mesoporous silica.
[0031] In one possible implementation, the mass ratio of the vinyl silicone oil to the filler premix slurry is 10:(2-4).
[0032] And / or, the temperature of the mixing system is 40℃-50℃;
[0033] And / or, the mass ratio of platinum in the slow-release catalyst to the vinyl silicone oil is (0.05-0.2):10000;
[0034] And / or, the flow rate of the inert atmosphere is 0.5 L / min to 2 L / min;
[0035] And / or, the hydrogen content of the hydrogen-containing silicone oil is 0.5%-1.2%;
[0036] And / or, the mass ratio of the hydrogen-containing silicone oil to the vinyl silicone oil is (5-15):100.
[0037] In one possible implementation, the heating and cooling cycle includes:
[0038] Heat to 130℃-140℃ at a first heating rate of 5℃ / min or higher and hold for 5min-10min.
[0039] Then, cool down to 100℃-110℃ at a first cooling rate of 3℃ / min or higher and hold for 5min-10min.
[0040] Then, increase the temperature to 150℃-160℃ at a second heating rate of 5℃ / min and hold for 10min-15min.
[0041] Then, cool down to 120℃-130℃ at a second cooling rate of 3℃ / min or higher and hold for 5min-10min.
[0042] Then, increase the temperature to 160℃-170℃ at a third heating rate of 5℃ / min and hold for 15min-20min.
[0043] And / or, the number of times is 2 to 3 times.
[0044] In one possible implementation, the post-processing includes constant temperature and humidity treatment, silicone oil bath treatment, and oven treatment.
[0045] In one possible implementation, the temperature of the constant temperature and humidity treatment is 23℃-27℃, the relative humidity of the constant temperature and humidity treatment is 60%-70%, and the time of the constant temperature and humidity treatment is 12h-24h.
[0046] And / or, the silicone oil treatment includes: placing the adhesive in silicone oil with a viscosity of 100 mPa•s-500 mPa•s and treating it at 80℃-100℃ for 1h-2h;
[0047] And / or, the temperature of the oven is 100℃-120℃, and the time of the oven treatment is 30min-60min.
[0048] In one possible implementation, the silicone oil includes methyl silicone oil, phenyl silicone oil, or ethyl silicone oil.
[0049] In one possible implementation, plasma surface treatment is further included after the post-processing.
[0050] Secondly, embodiments of this application provide a high-strength heat-resistant silicone rubber composite material, which is prepared by the above-described preparation method.
[0051] Thirdly, embodiments of this application provide a power fitting spacer bar, comprising the aforementioned high-strength heat-resistant silicone rubber composite material.
[0052] The high-strength heat-resistant silicone rubber composite material and its preparation method, as well as the power fitting spacer provided in this application, improve the dispersion uniformity of fillers and heat-resistant additives in the silicone rubber system and their interfacial stability with the matrix by pre-mixing and dispersing silane-modified silica with heat-resistant additives, and combining it with a supported platinum catalyst, pre-crosslinking under inert atmosphere conditions, and a secondary crosslinking reaction involving several heating and cooling cycles. At the same time, it improves the controllability of the crosslinking reaction and the uniformity of the crosslinking network, thereby reducing internal stress concentration in the material and improving the mechanical properties, heat resistance, and heat aging stability of the composite material. Detailed Implementation
[0053] Exemplary embodiments will be described in detail below. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with this application. Rather, they are merely examples of apparatuses and methods consistent with some aspects of this application as detailed in the appended claims.
[0054] Existing heat-resistant silicone rubber composites for power equipment are typically prepared using silicone rubber as the matrix, combined with inorganic fillers, heat-resistant additives, and addition crosslinking systems to achieve comprehensive performance that meets application requirements. The basic idea is to mix silicone rubber with fillers such as silica, then introduce heat-resistant additives and a catalytic system, forming an elastomer material with certain strength and heat resistance through a crosslinking reaction. However, in actual preparation, the inorganic fillers and silicone rubber matrix often rely primarily on physical blending, resulting in insufficient interfacial compatibility. This makes it difficult for the fillers to form a stable and uniform dispersion within the matrix; heat-resistant additives tend to accumulate or agglomerate in localized areas, making it difficult to uniformly construct a heat-resistant support structure within the material. Simultaneously, under conventional curing methods, the crosslinking reaction proceeds rapidly after initiation, making it difficult to achieve stable and controllable network growth within the system, easily leading to uneven crosslinking density distribution and internal stress accumulation. The aforementioned problems can further lead to phenomena such as interface debonding, local cracking, and accelerated performance degradation in materials under high-temperature aging and mechanical fatigue conditions. This makes it difficult for materials to simultaneously achieve high strength, stable heat resistance, and long-term service reliability, thus limiting their application stability in key power components.
[0055] The method for preparing high-strength heat-resistant silicone rubber composites provided in this application involves first mixing silane-modified silica with heat-resistant additives and dispersing the mixture in an organic solvent to form a filler premix slurry. Then, a platinum catalyst is loaded onto a support to obtain a slow-release catalyst. Subsequently, vinyl silicone oil is mixed with the filler premix slurry, and the slow-release catalyst and hydrogen-containing silicone oil are added under an inert atmosphere. A pre-crosslinking reaction and a secondary crosslinking reaction involving several heating and cooling cycles are then carried out sequentially. Finally, the resulting rubber compound is post-treated to obtain the high-strength heat-resistant silicone rubber composite material. This technical route achieves homogenization of the material structure, controllability of the crosslinking process, and synergistic improvement of overall performance through synergistic regulation of the filler system, catalytic system, crosslinking rhythm, and post-treatment process. This provides a more suitable preparation approach for heat-resistant silicone rubber composites used in power equipment, adaptable to long-term high-temperature and mechanically coupled service environments.
[0056] The technical solution of this application and how the technical solution of this application solves the above-mentioned technical problems are described in detail below with specific embodiments. The following specific embodiments can be combined with each other, and the same or similar concepts or processes may not be described again in some embodiments.
[0057] The method for preparing the high-strength heat-resistant silicone rubber composite material provided in this application includes:
[0058] Silane-modified silica was mixed with a heat-resistant additive and dispersed in an organic solvent to obtain a filler premixed slurry;
[0059] Platinum catalysts are supported on a support to obtain slow-release catalysts;
[0060] After mixing vinyl silicone oil with filler premix slurry, a slow-release catalyst is added to the resulting mixture, and hydrogen-containing silicone oil is added under an inert atmosphere to carry out pre-crosslinking reaction and secondary crosslinking reaction to obtain the adhesive; wherein, the secondary crosslinking reaction includes several heating and cooling cycles;
[0061] The rubber compound is post-treated to obtain a high-strength, heat-resistant silicone rubber composite material.
[0062] In some specific embodiments, silane-modified silicon oxide is prepared by a method including the following steps: mixing silicon oxide and silane coupling agent at a mass ratio of 100:(1-3) and stirring at 50℃-60℃ for 10min-20min to obtain silane-modified silicon oxide.
[0063] In some embodiments, the silicon oxide may be any one or a combination of fumed silica, precipitated silica, or micron-sized quartz powder.
[0064] In some embodiments, the silane coupling agent includes at least one of γ-methacryloxypropyltrimethoxysilane, γ-glycidyl etheroxypropyltrimethoxysilane, and γ-aminopropyltriethoxysilane.
[0065] Silane-modified silica refers to an inorganic filler that, after surface treatment with a silane coupling agent, forms a modified layer containing organic functional groups on the surface of silica particles. This improves the interfacial bonding between silica and the silicone rubber matrix and provides stable surface active sites for the loading and dispersion of subsequent heat-resistant additives. Its function is to transform the hydrophilic inorganic surface of the silica particles into an interfacial layer with organic phase compatibility through the coupling reaction of the silane coupling agent with the hydroxyl groups on the silica surface. This reduces the tendency of silica to agglomerate in the silicone oil system, enhances the synergistic bonding between silica and vinyl silicone oil and subsequent crosslinking networks, and improves the structural stability of the final material under high temperature and mechanical loads. In the overall preparation process, silane-modified silica is located in the pretreatment stage. It can be used as a separate modified filler in the subsequent mixing step with heat-resistant additives, or it can be directly mixed with heat-resistant additives to form a filler premix slurry after modification, and then mixed with vinyl silicone oil. It works together with subsequent components through physical dispersion, surface adsorption and interfacial coupling to form the dispersion framework in the subsequent pre-crosslinking and secondary crosslinking processes.
[0066] The preferred mass ratio of silicon oxide to silane coupling agent is 100:(1-3) to ensure that the silane coupling agent is sufficient to cover the surface of silicon oxide particles without forming an excessive free phase.
[0067] For example, the mass ratio of silicon oxide to silane coupling agent can be a range of 100:1, 100:2, 100:3, or any two of these.
[0068] Controlling the stirring temperature of the silica-silane coupling agent mixture at 50℃-60℃ allows the coupling reaction to proceed fully with minimal volatilization loss; controlling the stirring time at 10min-20min balances surface reaction rate and particle stability. The resulting modified layer is typically nanometer-thick, preferably in a monolayer or near-monolayer grafted state to avoid excessive thickness that could degrade subsequent dispersion performance. It should be understood that the above examples are merely illustrative and not limiting.
[0069] In some specific embodiments, the silane-modified silica is mixed with a heat-resistant additive and dispersed in an organic solvent, including: mixing the silane-modified silica and the heat-resistant additive at a mass ratio of 100:(5-10), stirring at 70℃-80℃ for 15min-30min, then adding an organic solvent and performing ultrasonic dispersion for 10min-30min to obtain a filler premixed slurry.
[0070] When silane-modified silica is mixed with heat-resistant additives and dispersed in an organic solvent, the heat-resistant additives refer to inorganic or semi-inorganic functional components that can improve the thermal stability of silicone rubber composites, inhibit thermo-oxidative aging, and improve long-term service performance under high-temperature conditions. These additives, together with the silane-modified silica, constitute the main dispersion system of the subsequent filler premix slurry. Their function and role are to allow the heat-resistant additives to preferentially adsorb or adhere to the surface of the modified silica through premixing and thermal stirring at a controlled temperature. Then, secondary depolymerization and uniform dispersion are achieved with the help of organic solvents and ultrasonic cavitation, thereby establishing a relatively stable composite microstructure at the filler level. This reduces the local enrichment and agglomeration of the heat-resistant additives in the subsequent silicone rubber matrix, improving the overall system's uniformity, flowability, and interfacial stability. The premixed filler slurry is positioned before the vinyl silicone oil in the overall preparation process. As an input component, it directly enters the subsequent mixing process and plays a decisive role in the distribution of the inorganic phase in the final crosslinked network. The transition between the filler slurry and the vinyl silicone oil is achieved through solvent carrying, wetting and spreading, and subsequent desolvation processes. It also maintains good spatial dispersion in the crosslinking system initiated by the slow-release catalyst and hydrogen-containing silicone oil.
[0071] Silane-modified silica and heat-resistant additives are mixed at a mass ratio of 100:(5-10) to ensure that the heat-resistant additives are uniformly attached to the surface of the modified silica at a low to medium load level; at the same time, the fluidity of the slurry and the ultrasonic dispersion effect are taken into account.
[0072] For example, the mass ratio of silane-modified silica to heat-resistant additive can be a range of 100:5, 100:6, 100:7, 100:8, 100:9, 100:10 or any combination thereof.
[0073] In some embodiments, the organic solvent may be at least one of anhydrous isopropanol, ethanol, and n-butanol.
[0074] Controlling the mixing and stirring temperature of silane-modified silica and heat-resistant additives at 70℃-80℃ can promote surface wetting and initial adsorption of the additives. Controlling the stirring time at 15min-30min can effectively weaken the secondary agglomeration between particles. Controlling the ultrasonic dispersion time at 10min-30min can further disperse weak agglomerates and form a stable suspension system through cavitation shearing.
[0075] In some embodiments, ultrasonic dispersion can be performed using either probe-type or trough-type ultrasonic dispersion, and the specific equipment type can be adjusted according to the batch size and viscosity.
[0076] It should be understood that the above examples are for illustrative purposes only and are not intended to be limiting.
[0077] In some embodiments, the heat-resistant additive includes at least one of cerium oxide, titanium oxide, and cerium hydroxide.
[0078] Cerium oxide particles have high thermal stability and free radical quenching ability, and can be uniformly loaded onto the modified silica surface as a heat-resistant support phase; in another possible embodiment, the heat-resistant additive is titanium oxide or cerium hydroxide, which can maintain structural stability at high temperatures and improve the heat deformation resistance of the composite material.
[0079] In the above-mentioned process of preparing the filler premix slurry, silica is first fully contacted and stirred with a silane coupling agent at a controlled temperature of 50℃-60℃, allowing the hydrolyzable groups in the coupling agent molecules to react with the active sites on the silica surface, thereby forming a silane-modified layer with organic affinity on the particle surface. Subsequently, the obtained silane-modified silica is mixed with a heat-resistant additive at a predetermined mass ratio and continuously stirred at 70℃-80℃, allowing the heat-resistant additive to preferentially spread and adsorb onto the modified particle surface. Then, an organic solvent is added and ultrasonic dispersion is performed for 10-30 minutes, causing the agglomerates between particles to be deagglomerated, wetted, and forming a uniform and stable filler premix slurry. When this premix slurry enters the subsequent mixing stage with vinyl silicone oil, it can participate in the construction of the pre-crosslinking and secondary crosslinking network with a more uniform microscopic distribution, thereby reducing the risk of local aggregation of inorganic fillers and heat-resistant additives, enhancing the interfacial stability between the filler and the silicone rubber matrix, and slowing down the performance degradation under high-temperature aging and mechanical fatigue conditions. Based on the above analysis, this step achieves filler surface activation, uniform loading of heat-resistant additives, and stable dispersion of the system, which is beneficial to improving the overall uniformity, thermal stability, and long-term service reliability of the final high-strength heat-resistant silicone rubber composite material.
[0080] In some specific embodiments, the support includes a first support and a second support, wherein the pore size of the first support is greater than or equal to the pore size of the second support; the sustained-release catalyst includes a first sustained-release catalyst and a second sustained-release catalyst.
[0081] The first and second supports are used to load platinum catalytic components and construct a graded slow-release catalytic system, respectively. The first support is a support with a relatively open pore structure, a relatively weak adsorption and binding effect on the platinum catalytic components, and is more conducive to the release of catalytic activity at low temperatures. The second support is a support with a relatively dense pore structure, a stronger confinement effect on the platinum catalytic components, and is more conducive to the gradual release of catalytic activity at higher temperatures or longer holding times.
[0082] The function and role of this structure is to regulate the loading state, diffusion path and release rate of platinum catalyst by different pore size supports, so that the first and second slow-release catalysts play different degrees of catalytic role in the pre-crosslinking reaction and the secondary crosslinking reaction, thereby realizing the segmented start-up and smooth progress of the crosslinking reaction and reducing the probability of rapid gelation of the system in local areas.
[0083] The first and second carriers are usually added to the catalytic system in the form of solid particles. After loading the platinum catalyst, they participate in the subsequent mixing process together with vinyl silicone oil, hydrogen-containing silicone oil and filler premixed slurry. The two can be fed at the same mixing stage, or they can be introduced one after the other according to the process requirements to meet the cycle requirements of low temperature pre-crosslinking and high temperature cyclic crosslinking. The working interface between them and the main system is mainly formed through dispersion contact and thermal activation release.
[0084] Before the pre-crosslinking reaction begins, the first and second slow-release catalysts are dispersed sequentially or simultaneously in the premixed slurry of vinyl silicone oil and filler. Due to its relatively large pore size, the first support can release its supported platinum catalytic component more quickly at lower temperatures, thus preferentially initiating the initial hydrosilylation reaction within the system and forming a uniform pre-crosslinked network during the pre-crosslinking reaction stage. Simultaneously, the second support, with its smaller pore size, has a stronger confinement effect on the platinum catalytic component, resulting in a relatively delayed release of its catalytic activity. During the pre-crosslinking stage, it primarily serves to reserve catalytic capacity and stabilize the system's reaction rate. As the system enters the secondary crosslinking reaction and undergoes several heating and cooling cycles, the increasing temperature causes the platinum catalytic component in the second support to gradually desorb and participate in subsequent crosslinking. The first and second slow-release catalysts form complementary catalysis at different temperature stages, allowing the crosslinking reaction to proceed continuously from the surface inwards and from fast to slow, thereby making the internal network structure of the compound more uniform and reducing local over-crosslinking, under-crosslinking, and internal stress concentration.
[0085] Based on the above analysis, it can be seen that the graded loading and graded release catalytic system can effectively improve the uniformity of catalytic activity distribution, enhance the controllability of pre-crosslinking and secondary crosslinking processes, and help obtain high-strength heat-resistant silicone rubber composite materials with more stable interfacial bonding, more moderate performance degradation after thermal aging, and higher long-term service reliability.
[0086] In some specific embodiments, the platinum catalyst is supported on a support, including:
[0087] The platinum catalyst was dispersed in an alcohol solvent to obtain a platinum catalyst dispersion.
[0088] According to the mass ratio of platinum catalyst to first support of (1-5):100, the first support is added to the platinum catalyst dispersion and impregnated for 12h-24h, with stirring at regular intervals during the period, and then filtered and dried to obtain the first slow-release catalyst.
[0089] The second support was added to the platinum catalyst dispersion at a mass ratio of (1-5):100, and impregnated for 12-24 hours with periodic stirring. The mixture was then filtered and dried to obtain the second slow-release catalyst.
[0090] In this application, the process of supporting a platinum catalyst refers to first uniformly dispersing the catalytically active platinum component in an alcohol solvent, and then, through the pore adsorption, capillary permeation, and surface anchoring effects of the support, fixing the platinum component in a relatively stable spatial distribution on the surface and internal channels of the first and second supports. Its function and effect are to reduce the probability of direct contact and local enrichment of platinum in the subsequent silicone rubber system by dispersing and loading the platinum component, allowing the catalytic centers to participate in the crosslinking reaction in a relatively uniform and confined state, thereby avoiding localized excessively rapid crosslinking, sudden changes in crosslinking density, and internal stress concentration in the initial mixing or heating stages of the system.
[0091] By controlling the mass ratio of platinum catalyst to both the first and second supports during impregnation to (1-5):100, sufficient loading can be ensured while avoiding excessive accumulation of platinum components. The impregnation time is 12-24 hours to ensure that the platinum components in the solution have enough time to enter the pores of the support and achieve diffusion equilibrium. Timely stirring during this period is used to maintain a uniform concentration distribution in the system and reduce uneven loading caused by local concentration differences. Filtration and drying are used to remove excess solvent and fix the platinum components on the support. Filtration can be carried out using conventional vacuum filtration or gravity filtration, and drying can be carried out using hot air drying, vacuum drying, or low-temperature reduced pressure drying to improve loading stability while avoiding platinum component migration.
[0092] For example, the mass ratio of the platinum catalyst to the first support can be 1:100, 2:100, 3:100, 4:100, 5:100 or any combination thereof; the mass ratio of the platinum catalyst to the second support can be 1:100, 2:100, 3:100, 4:100, 5:100 or any combination thereof.
[0093] It should be noted that the mass ratio of platinum catalyst to the first support and the mass ratio of platinum catalyst to the second support may be the same or different.
[0094] In some specific implementations, the pore size of the first carrier is 2nm-10nm.
[0095] In some specific implementations, the pore size of the second carrier is 2nm-5nm.
[0096] By classifying the pore sizes of two types of supports, differences in the adsorption strength, intrapore diffusion resistance, and thermal response release behavior of platinum catalysts in different pore systems are created, thus forming a first-type and a second-type slow-release catalyst, respectively. When the pore size of the first support is 2nm-10nm, its pores can accommodate the entry of platinum catalyst molecules or particles, stable adsorption, and subsequent controllable desorption under heating conditions, making it suitable for providing a relatively gentle catalytic effect in the pre-crosslinking stage. When the pore size of the second support is 2nm-5nm, its smaller pore size and typically higher specific surface area enable the platinum catalyst to form stronger interfacial bonding and more significant diffusion hindrance, thereby releasing more concentrated catalytic activity in the secondary crosslinking stage or after temperature rise.
[0097] For example, the pore size of the first carrier can be a range of 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm or any combination thereof; the pore size of the second carrier can be a range of 2nm, 3nm, 4nm, 5nm or any combination thereof.
[0098] In some specific embodiments, the mass ratio of the first sustained-release catalyst to the second sustained-release catalyst is (4-6):(4-6).
[0099] By adjusting the mass ratio of the first and second slow-release catalysts, the vulcanization kinetics can be precisely controlled, the catalytic activity and stability can be balanced, and the cross-linked network structure of silicone rubber can be optimized. Ultimately, this achieves a comprehensive effect of a wide processing window, excellent mechanical properties, good thermal stability, and high appearance quality, while reducing the amount of platinum used and the cost.
[0100] The mass ratio of the first and second slow-release catalysts can be set according to the ratio of vinyl silicone oil and hydrogen-containing silicone oil in the system and the pre-crosslinking time window. It can usually be adjusted around a ratio of approximately 1:1 to ensure that the catalytic contributions of the two stages are interconnected. Alternatively, it can be biased towards one side according to the desired temperature response curve to enhance the reaction rate of a certain stage.
[0101] In some specific embodiments, the platinum catalyst includes at least one of chloroplatinic acid, platinum-divinyltetramethyldisiloxane complex, and platinum-cyclohexene complex.
[0102] In some specific embodiments, the first carrier includes at least one of mesoporous silica, mesoporous alumina, mesoporous silica-alumina composite, and molecular sieve.
[0103] The first support can be mesoporous silica, which has regular channels, narrow pore size distribution and many surface hydroxyl groups, making it easy for the platinum catalyst to enter the pores through impregnation and obtain a relatively stable loading state. In another possible embodiment, the first support can be ordered mesoporous alumina or mesoporous silica-alumina composite material, which has good pore connectivity and high structural stability under thermal conditions, which is conducive to achieving continuous slow release. In yet another possible embodiment, the first support can also be a mesoporous carbon material prepared by template method, which has good thermal conductivity of pore walls and adjustable pore structure, which can improve the dispersion uniformity of the catalyst while maintaining the mechanical stability of the support.
[0104] In some specific embodiments, the second carrier includes at least one of activated carbon and mesoporous alumina.
[0105] For the second carrier, activated carbon can be used, which has a high proportion of micropores and small to mesopores, strong adsorption capacity, and is suitable for forming a strongly bound catalytic reservoir. In another possible embodiment, mesoporous silica or activated carbon materials can be used to obtain a smaller average pore size and higher pore volume utilization efficiency. In yet another possible embodiment, porous metal oxides that have been acid-washed or alkali-activated can also be used to achieve more suitable release behavior according to different process requirements.
[0106] In this application, the mixed system for pre-crosslinking and secondary crosslinking reactions refers to a reaction system composed of vinyl silicone oil, filler premixed slurry, slow-release catalyst, and hydrogen-containing silicone oil, used to complete the pre-crosslinking and secondary crosslinking of silicone rubber base material under an inert atmosphere. The function of this mixed system is to provide a uniform material environment for the hydrosilylation reaction, and through the coordinated control of temperature, catalyst concentration, gas protection intensity, and crosslinking agent ratio, to enable the system to form a moderate and controllable initial network in the pre-crosslinking stage, thereby providing a stable foundation for subsequent secondary crosslinking under multiple heating and cooling cycles.
[0107] The mixing system is typically housed in a reactor equipped with a jacketed temperature control structure and an inert gas introduction structure. The reactor's inner wall, in conjunction with the stirring assembly, forms a closed or semi-closed working space. The slow-release catalyst, vinyl silicone oil, and hydrogen-containing silicone oil are metered and introduced through either a top or side feed port, and thoroughly mixed under the action of the stirring blades. The inert gas enters above the liquid surface or into the liquid phase via a gas distribution pipe or gas dispersion head to achieve displacement and protection. This mixing system can morphologically exhibit as a low-viscosity fluid, a semi-gel state, or a gradually thickening elastic precursor.
[0108] In some specific embodiments, the mass ratio of vinyl silicone oil to filler premix slurry is 10:(2-4).
[0109] By adjusting the mass ratio of vinyl silicone oil to filler premixed slurry to 10:(2-4), the viscosity of the resulting reaction system is adapted to the subsequent processing technology, and the filler is uniformly dispersed in vinyl silicone oil, so as to match the release rate and sulfidation rate of platinum in the slow-release catalyst, thereby obtaining a more uniform and dense cross-linked network and filler-reinforcing network.
[0110] For example, the mass ratio of vinyl silicone oil to filler premixed slurry is a range of 10:2, 10:2.5, 10:3, 10:3.5, 10:4, or any combination thereof.
[0111] In some specific implementations, the temperature of the mixing system is 40°C-50°C.
[0112] When the temperature is controlled at 40℃-50℃, the system can maintain a controllable reaction rate under a low heat load, avoiding localized rapid gelation.
[0113] In some specific embodiments, the mass ratio of platinum in the slow-release catalyst to vinyl silicone oil is (0.05-0.2):10000.
[0114] When the mass ratio of platinum to vinyl silicone oil is limited to (0.05-0.2):10000, structural inhomogeneity caused by excessively rapid reaction can be suppressed while ensuring catalytic activity.
[0115] For example, the mass ratio of platinum to vinyl silicone oil can be a range of 0.05:10000, 0.1:10000, 0.15:10000, 0.2:10000, or any combination thereof.
[0116] In some specific implementations, the flow rate of the inert gas is 0.5 L / min to 2 L / min.
[0117] By controlling the inert gas flow rate between 0.5 L / min and 2 L / min, a continuous and effective displacement protection can be achieved, while avoiding disturbances to the system interface and local temperature field caused by excessive airflow.
[0118] For example, the flow rate of the inert gas can be a range of 0.5 L / min, 1.0 L / min, 1.5 L / min, 2.0 L / min, or any combination thereof.
[0119] In some specific implementations, the hydrogen content of the hydrogen-containing silicone oil is 0.5%-1.2%.
[0120] When the hydrogen content of the hydrogen-containing silicone oil used is 0.5%-1.2%, it can meet the supply of active hydrogen required for the crosslinking reaction without causing excessive crosslinking due to excessive active groups.
[0121] For example, the hydrogen content of the hydrogen-containing silicone oil can be a range of 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, or any combination thereof.
[0122] In some specific embodiments, the mass ratio of hydrogen-containing silicone oil to vinyl silicone oil is (5-15):100.
[0123] When the mass ratio of hydrogen-containing silicone oil to vinyl silicone oil is (5-15):100, the network formation density can be within a suitable window, thus balancing initial processability and final strength.
[0124] For example, the mass ratio of hydrogen-containing silicone oil to vinyl silicone oil can be 5:100, 7:100, 9:100, 11:100, 13:100, 15:100 or any combination thereof.
[0125] When preparing the reaction system, a premixed slurry of vinyl silicone oil and filler is first added to the reactor, and the mixture is kept in thermal equilibrium at a temperature of 40℃-50℃ to ensure that the viscosity is within a range suitable for uniform mass transfer. Then, a slow-release catalyst loaded with a low platinum amount is added and uniformly dispersed in the system under stirring. Oxygen and water vapor are removed from the reactor under continuous protection with an inert gas flow rate of 0.5L / min-2L / min to reduce the risk of oxidation, side reactions, and catalytic deactivation. During this process, the mass ratio of platinum to vinyl silicone oil is controlled at (0.05-0.2):10000, which allows the hydrosilylation reaction to start at a relatively gentle rate and form a relatively uniformly distributed pre-crosslinked structure. Subsequently, hydrogen-containing silicone oil is added, with a hydrogen content limited to 0.5%-1.2%, and its mass ratio to vinyl silicone oil is controlled at (5-15):100, ensuring that the active hydrogen forms a number of matching crosslinking nodes with the vinyl groups. Within this temperature and atmosphere window, the reaction system will not thicken abruptly due to excessively rapid catalysis, nor will the reaction stagnate due to insufficient temperature. This allows for the establishment of a continuous and stable initial network in the pre-crosslinking stage, and provides a uniform reaction basis for subsequent secondary crosslinking, which involves several heating and cooling cycles.
[0126] Based on the above analysis, it can be seen that by jointly limiting the temperature of the mixing system, the platinum content of the catalyst, the flow rate of the inert gas, and the composition and ratio of the hydrogen-containing silicone oil, the controllability of the crosslinking process and the uniformity of the system can be effectively improved, the probability of local over-crosslinking, structural defects and internal stress accumulation can be reduced, and thus it is beneficial to obtain high-strength heat-resistant silicone rubber composite materials with stable mechanical properties, good heat aging resistance and suitable for long-term service of power equipment.
[0127] In some specific embodiments, the heating and cooling cycle includes: heating to 130℃-140℃ at a first heating rate of 5℃ / min and holding for 5min-10min; cooling to 100℃-110℃ at a first cooling rate of 3℃ / min and holding for 5min-10min; heating to 150℃-160℃ at a second heating rate of 5℃ / min and holding for 10min-15min; cooling to 120℃-130℃ at a second cooling rate of 3℃ / min and holding for 5min-10min; and heating to 160℃-170℃ at a third heating rate of 5℃ / min and holding for 15min-20min.
[0128] The heating and cooling cycle is a temperature control procedure for the secondary crosslinking reaction. It is defined by using multiple temperature platforms and heating / cooling transition sections to cure the pre-crosslinked adhesive in stages, thereby allowing the hydrosilylation reaction to proceed gradually in different temperature zones and to rearrange the network structure in stages.
[0129] This procedure targets pre-crosslinked adhesive compounds containing vinyl silicone oil, hydrogen-containing silicone oil, slow-release catalysts, and dispersed filler premixed slurry. Under thermal action, the components continue to form crosslinks and solidify through chain segment entanglement. The resulting crosslinked network evolves sequentially from sparse to dense at different temperature platforms. This temperature control procedure is typically implemented in programmed temperature-controlled ovens, hot press molds, reaction vessels, or continuous heating devices. The adhesive compound can be spread on a tray, placed in a mold cavity, or kept within a closed reaction space to ensure heating uniformity and atmosphere stability.
[0130] The first heating rate, the first cooling rate, the second heating rate, the second cooling rate, and the third heating rate are used to control the release of reaction heat and the evolution of internal stress, respectively. The first heating stage enables the system to quickly cross the low-temperature activation region and initiate the formation of slower cross-linking bonds. The first cooling stage is used to temporarily suppress the reaction rate and promote local relaxation of chain segments. The second heating stage enables more active sites to participate in the reaction and improves the integrity of the initial network. The second cooling stage further releases the internal stress caused by volume shrinkage and cross-linking shrinkage. The third heating stage completes the full improvement of cross-linking degree and network stabilization on a high-temperature platform of 160℃-170℃.
[0131] In the above embodiments, the target temperature of the first heating stage is 130℃-140℃, and the holding time is 5min-10min. This stage allows the catalytic system to gradually reach an effective activation state and promotes a more uniform temperature distribution between the surface and interior of the adhesive. The target temperature of the first cooling stage is 100℃-110℃, and the holding time is 5min-10min. This stage is used to mitigate the temperature difference between the inside and outside of the system without significantly interrupting the crosslinking process, and to reduce the internal stress concentration caused by rapid curing. The target temperature of the second heating stage is 150℃-160℃. The first cooling stage has a target temperature of 120℃-130℃ and a holding time of 5min-10min. This stage allows the cross-linking reaction to continue and the network structure to develop towards a higher cross-linking density. The second cooling stage has a target temperature of 120℃-130℃ and a holding time of 5min-10min. This stage continues to disperse thermal stress and promotes the reorientation of unreacted chain segments. The third heating stage has a target temperature of 160℃-170℃ and a holding time of 15min-20min. This stage is used to complete the final curing and shaping, so that a more stable cross-linked network structure is formed inside the material.
[0132] The aforementioned temperature plateau and time parameters can be adjusted appropriately based on the thickness of the rubber compound, the filling amount, and the heat transfer efficiency of the equipment, but the basic logic of segmented heating and cooling and multiple cycles should remain unchanged. The first, second, and third heating rates should all be no less than 5°C / min to ensure sufficient reaction driving force for temperature plateau switching; the first and second cooling rates should both be no less than 3°C / min to provide necessary relaxation time for the rubber compound while maintaining the production cycle. Through the above procedure, the cross-linking reaction inside the material no longer relies on a single high temperature instantaneous completion, but is completed gradually in multiple temperature zones, which is conducive to the formation of a uniform cross-linking gradient and a more continuous network structure.
[0133] In some specific implementations, the above-mentioned heating and cooling cycles are performed 2 to 3 times.
[0134] When the curing process is preferably repeated 2 to 3 times, a relatively stable balance can be formed between reaction advancement and stress release, avoiding local over-crosslinking, heat accumulation and interface damage caused by one-time high-temperature curing.
[0135] In some specific implementations, post-processing includes constant temperature and humidity treatment, silicone oil bath treatment, and oven treatment.
[0136] Constant temperature and humidity treatment refers to placing the cross-linked rubber compound in a constant temperature and humidity environment and maintaining it at a preset temperature and relative humidity for a period of time to achieve a balance in the internal moisture distribution, chain segment relaxation state, and residual reactive group state of the material; silicone oil bath treatment refers to immersing the above-mentioned rubber compound in a silicone oil medium, which further promotes the filling of micropores, surface densification, and residual stress release of the material through medium wetting and heat transfer; oven treatment refers to transferring the rubber compound after silicone oil bath treatment into an oven for heating and drying to remove surface and internal residual medium and complete structural stabilization.
[0137] The above three components together constitute a stabilization unit for post-crosslinked adhesives. Its function is to promote the slow condensation of trace active groups still present in the material without changing the main crosslinking network, reduce the internal stress gradient caused by rapid curing, and improve the dimensional stability and heat aging resistance of the material under the coupled effects of high temperature, humid heat and mechanical load.
[0138] The constant temperature and humidity treatment, silicone oil bath treatment, and oven treatment are all performed after the secondary crosslinking reaction is completed and before the final product output. The three can be implemented sequentially according to the process order, or the holding time can be adjusted according to the thickness of the rubber compound, the molding size, and the residual stress level. The constant temperature and humidity treatment is usually performed before the silicone oil bath treatment in order to achieve humidity and heat balance first. Then, the internal filling is further enhanced by silicone oil wetting. Finally, the oven treatment completes the evaporation of the medium and the heat curing. The three are connected by transfer containers, impregnation carriers, or pallets.
[0139] The equipment used for constant temperature and humidity treatment can be an environmental chamber, a sealed curing room, or a programmable temperature and humidity control chamber with a closed-loop temperature and humidity control system. Its lining can be stainless steel plate, corrosion-resistant composite plate, or polymer coated plate. The equipment used for silicone oil bath treatment can be an oil bath tank with a constant temperature heating jacket, a circulating immersion tank, or an impregnation tank with a stirring and temperature equalization mechanism. Its tank body can be made of stainless steel, glass enamel, or heat-resistant alloy material. The silicone oil medium can be low-viscosity, medium-viscosity, or high-viscosity heat-resistant silicone oil. The equipment used for oven treatment can be a hot air circulating oven, a vacuum oven, or a zoned temperature-controlled oven.
[0140] The temperature, time, and medium dosage of constant temperature and humidity treatment, silicone oil bath treatment, and oven treatment can all be matched according to the thickness, cross-sectional size, and loading amount of the rubber compound. For example, thin-walled samples can use a shorter holding time and a smaller medium liquid depth, while thick-walled or large-volume samples need to have a longer treatment time and a greater immersion depth to ensure uniform treatment. In the silicone oil bath, the silicone oil level should usually be higher than the surface of the rubber compound to form sufficient wetting conditions. The hot air circulation space in the oven should ensure that there are gaps between the samples to avoid local overheating or uneven heating.
[0141] In some specific implementations, the temperature for constant temperature and humidity treatment is 23℃-27℃, the relative humidity is 60%-70%, and the treatment time is 12h-24h.
[0142] For example, the temperature of the constant temperature and humidity treatment can be a range of 23°C, 24°C, 25°C, 26°C, 27°C or any combination thereof; the relative humidity of the constant temperature and humidity treatment can be a range of 60%, 65%, 70% or any combination thereof; and the time of the constant temperature and humidity treatment can be a range of 12h, 14h, 16h, 18h, 20h, 22h, 24h or any combination thereof.
[0143] In some specific embodiments, the silicone oil treatment includes: placing the adhesive in silicone oil with a viscosity of 100 mPa•s-500 mPa•s and treating it at 80℃-100℃ for 1h-2h.
[0144] The viscosity of the silicone oil used is controlled between 100 mPa•s and 500 mPa•s to balance flowability, thermal conductivity, and surface wetting ability.
[0145] For example, the viscosity of the silicone oil can be a range of 100 mPa•s, 200 mPa•s, 300 mPa•s, 400 mPa•s, 500 mPa•s or any two of these; the temperature for silicone oil treatment can be a range of 80°C, 85°C, 90°C, 95°C, 100°C or any two of these.
[0146] The amount of silicone oil used should be sufficient to completely immerse the adhesive to be treated or fully cover the surface to be treated, and form a continuous and stable liquid phase surrounding layer in the treatment tank to ensure uniform heating of all parts during the post-treatment process.
[0147] In some specific implementations, the oven temperature is 100℃-120℃ and the oven time is 30min-60min.
[0148] In some specific embodiments, the silicone oil includes methyl silicone oil, phenyl silicone oil, or ethyl silicone oil.
[0149] Silicone oil is an organosilicon liquid medium used in post-treatment silicone oil baths. Its function is to transfer heat, wet and penetrate, and balance stress on the surface and near-surface area of the material after the adhesive has undergone pre-crosslinking molding. This fills local micropores, weakens surface defects generated during curing, and reduces residual internal stress on the surface of the adhesive caused by temperature gradient changes.
[0150] Silicone oil is usually placed inside the post-processing container, in direct contact with or covering the surface of the adhesive to be treated, and the required temperature is maintained by a heating device, so that the silicone oil transfers heat to the adhesive under constant or controllable temperature rise conditions; the adhesive is usually placed below the surface of the silicone oil in order to form a relatively uniform immersion processing environment.
[0151] Methyl silicone oil, phenyl silicone oil, or ethyl silicone oil can be used alone or in combination according to process requirements. In one possible embodiment, methyl silicone oil can be in the form of linear polydimethylsiloxane liquid, which has good fluidity and process compatibility. In another possible embodiment, phenyl silicone oil can improve the high-temperature stability and thermal oxidation resistance of the medium by introducing a phenyl structure, making it suitable for post-processing with high heat resistance requirements. In yet another possible embodiment, ethyl silicone oil can improve the surface condition of the compound by adjusting the wettability, permeability, and volatile residue behavior of the medium through its side group structure.
[0152] In some specific implementations, plasma surface treatment is also included after post-processing.
[0153] Plasma surface treatment utilizes high-energy particles to bombard the material surface, inducing the rearrangement of surface molecular chain segments and forming active groups, further releasing residual surface stress, and increasing surface polarity. This enhances the bonding ability with adhesive layers, coatings, overlays, or assembly interfaces, and reduces the risk of debonding, peeling, or localized detachment caused by insufficient interface energy during long-term service.
[0154] Plasma surface treatment specifically includes: placing the sample in a low-temperature plasma treatment device, evacuating to a working pressure of 20Pa-100Pa, introducing a treatment gas (argon or an argon / oxygen mixture, with a mixing ratio of Ar:O2=95:5), a gas flow rate of 10 sccm-30 sccm, turning on the radio frequency power supply, and setting the discharge power to 50W-150W (power density 0.5-2W / cm³). 2 The treatment time is 1-5 minutes. After treatment, the sample is removed by venting. Preferably, the treated sample should be coated or bonded within 4 hours to fully utilize the surface-active groups.
[0155] Plasma penetration depth is typically controlled to be effective only on the surface. Processing power, gas flow rate, processing distance, and residence time should be matched according to material thickness, surface curvature, and target wettability. The general principle is to avoid causing significant etching, surface whitening, or embrittlement. For example, in a vacuum chamber, lower power, shorter processing time, and moderate gas pressure can be used. In atmospheric pressure jetting, the treatment dose per unit area can be controlled by adjusting the distance between the nozzle and the sample surface, the scanning speed, and the coverage width.
[0156] The method for preparing high-strength heat-resistant silicone rubber composite material provided in this application involves first dispersing silane-modified silica and heat-resistant additives in an organic solvent to form a filler premix slurry. This allows the inorganic filler to complete wetting, depolymerization, and surface activation before entering the main reaction system. The catalytic activity is controlled by supporting a platinum catalyst. Then, vinyl silicone oil and hydrogen-containing silicone oil undergo pre-crosslinking under an inert atmosphere and secondary crosslinking through multiple heating and cooling cycles. This allows the crosslinked network to grow gradually and form a relatively uniform gradient structure, thereby improving the interfacial bonding between the filler and the matrix, reducing stress concentration caused by excessively rapid local crosslinking, and inhibiting interfacial debonding, local cracking, and performance degradation under high-temperature aging conditions. Simultaneously, post-treatment further eliminates residual solvents and internal stress, stabilizes the network configuration, and improves the material's thermal stability, mechanical strength, and long-term service reliability. This makes the resulting composite material more suitable for use under long-term high-temperature, mechanical load, and outdoor environmental conditions.
[0157] This application also provides a high-strength heat-resistant silicone rubber composite material prepared by the above preparation method.
[0158] This high-strength, heat-resistant silicone rubber composite material, prepared using the aforementioned method, allows for relatively uniform dispersion of silane-modified silica and heat-resistant additives within the matrix, enhancing the interfacial bonding between the filler and silicone rubber, thereby reducing the risk of localized agglomeration and interfacial debonding. The slow-release catalyst, combined with the pre-crosslinking reaction and the secondary crosslinking reaction involving several heating and cooling cycles, ensures more stable and controllable crosslink network growth, further reducing uneven crosslink density distribution and internal stress accumulation. Therefore, this composite material exhibits high tensile strength, tear strength, and elastic recovery, while maintaining good dimensional stability, structural integrity, and heat aging resistance under the combined effects of high temperature, mechanical load, and outdoor aging.
[0159] This application also provides a power fitting spacer bar, comprising the aforementioned high-strength heat-resistant silicone rubber composite material.
[0160] By using high-strength, heat-resistant silicone rubber composite material as the key structural or coating material, the aforementioned power fitting spacers maintain high mechanical strength and elastic recovery under long-term current-carrying temperature rise, conductor galloping, and outdoor damp heat aging conditions, thus reducing the likelihood of deformation, cracking, and interface instability. Due to the more uniform internal structure, more stable filler interface bonding, and more controllable cross-linking network of this composite material, the spacers maintain dimensional stability and insulation sealing reliability even under the coupled effects of high temperature and mechanical loads. This improves the heat aging resistance and long-term service safety of power fittings, making them more suitable for harsh conditions such as power transmission lines.
[0161] The power fitting spacer provided in this embodiment can perform the method provided in the above method embodiment. Its implementation principle and technical effect are similar, and will not be described in detail here.
[0162] The technical solution of this application will be further described below using specific embodiments.
[0163] Example 1
[0164] A high-strength, heat-resistant silicone rubber composite material is prepared as follows:
[0165] Silica and γ-methacryloxypropyltrimethoxysilane were mixed at a ratio of 100:1 and stirred at 50°C for 20 min to obtain silane-modified silica. Silane-modified silica was then mixed with nano-cerium oxide at a ratio of 100:5 and stirred at 70°C for 15 min. Anhydrous isopropanol was then added, and the mass ratio of anhydrous ethanol to silica was 1:2. The mixture was ultrasonically dispersed for 15 min to obtain a filler premix slurry.
[0166] Chloroplatinic acid was dissolved in anhydrous ethanol to prepare a platinum catalyst dispersion with a concentration of 0.05 g / ml. Mesoporous silica SBA-15 (pore size of 3 nm) was used as the first support. The first support was added to the platinum catalyst dispersion at a mass ratio of 100:5 to the first support. The mixture was impregnated at room temperature for 12 h, and stirred every 4 h. The mixture was then filtered, and the solid obtained by filtration was vacuum dried at 60 °C for 8 h to obtain the first slow-release catalyst.
[0167] Chloroplatinic acid was dissolved in anhydrous ethanol to prepare a platinum catalyst dispersion with a concentration of 0.01 g / ml. Wood-based activated carbon (ash content <1%, pre-boiled with 10% nitric acid solution for 1 h, washed with deionized water until neutral and dried, pore size 2 nm) was used as the second support. The second support was added to the platinum catalyst dispersion at a mass ratio of 100:1 to the second support. The mixture was impregnated at room temperature for 12 h, stirred every 4 h, and then filtered. The solid obtained by filtration was vacuum dried at 60 °C for 8 h to obtain the second slow-release catalyst.
[0168] Vinyl silicone oil and filler premix slurry (the mass ratio of vinyl silicone oil to filler premix slurry is 10:2) are mixed and cooled to 40°C. A slow-release catalyst (the first slow-release catalyst and the second slow-release catalyst are mixed at a mass ratio of 1:1) is added. The mass ratio of platinum in the slow-release catalyst to vinyl silicone oil is 0.05:10000. At the same time, nitrogen gas is introduced at a flow rate of 0.5 L / min. After stirring for 10 min, hydrogen-containing silicone oil with a hydrogen content of 1.2% is added, and the amount added is 5% of the mass of vinyl silicone oil. Stirring is continued, and a pre-crosslinking reaction is carried out for 60 min to obtain a pre-crosslinked adhesive.
[0169] The pre-crosslinked compound is subjected to secondary crosslinking using a pulse heating mode. The pulse heating process consists of two cycles, each consisting of the following steps:
[0170] Heat to 130℃ at a first heating rate of 5℃ / min and hold for 5min;
[0171] Cool to 100℃ at a first cooling rate of 3℃ / min and hold for 5 minutes;
[0172] Heat to 150℃ at a second heating rate of 5℃ / min and hold for 10 min;
[0173] Cool to 120℃ at a second cooling rate of 3℃ / min and hold for 5 minutes;
[0174] The mixture is heated to 160°C at a first heating rate of 5°C / min and held for 15 min to obtain the adhesive compound.
[0175] The rubber compound was subjected to constant temperature and humidity treatment at 25℃±2℃ and 60% relative humidity for 12 hours; then it was placed in methyl silicone oil with a viscosity of 100mPa·s for silicone oil bath treatment; and then it was placed in an oven at 100℃ for 30 minutes to obtain a high-strength heat-resistant silicone rubber composite material.
[0176] Example 2
[0177] A high-strength, heat-resistant silicone rubber composite material is prepared using a method essentially the same as in Example 1, except that the mass ratio of silicon oxide to γ-methacryloxypropyltrimethoxysilane is 100:3; the mass ratio of silane-modified silicon oxide to nano-cerium oxide is 100:10; the mass ratio of silicon oxide to anhydrous ethanol is 10:8; during platinum catalyst impregnation, the mass ratio of the first support to platinum chlorate is 100:1, and the mass ratio of the second support to platinum chlorate is 100:5; the mass ratio of the first slow-release catalyst to the second slow-release catalyst is 1:2; the mass ratio of vinyl silicone oil to filler premixed slurry is 10:4; the mass ratio of platinum to vinyl silicone oil in the slow-release catalyst is 0.2:10000; and the mass ratio of hydrogen-containing silicone oil (0.5% hydrogen content) to vinyl silicone oil is 15:100.
[0178] Example 3
[0179] A high-strength heat-resistant silicone rubber composite material is prepared in a manner similar to that of Example 1, except that the mass ratio of silicon oxide to γ-methacryloxypropyltrimethoxysilane is 100:0.5; the mass ratio of silane-modified silicon oxide to nano-cerium oxide is 100:4; the mass ratio of platinum to vinyl silicone oil in the slow-release catalyst is 0.04:10000; the mass ratio of hydrogen-containing silicone oil to vinyl silicone oil is 4:100, and the hydrogen content of the hydrogen-containing silicone oil used is 1.3%.
[0180] In this embodiment, the mass ratio of hydrogen-containing silicone oil to vinyl silicone oil was reduced from 5:100 in Example 1 to 4:100, while the hydrogen content of the hydrogen-containing silicone oil was increased from 1.2% in Example 1 to 1.3%, so that the total amount of active hydrogen in the system remained basically consistent with that in Example 1. This eliminated the interference of changes in the total amount of crosslinking agent on the results and ensured that the performance difference mainly stemmed from changes in the amount of coupling agent, the proportion of heat-resistant additives, and the amount of platinum catalyst.
[0181] Example 4
[0182] A high-strength heat-resistant silicone rubber composite material is prepared in a manner similar to that of Example 2, except that the mass ratio of silicon oxide to γ-methacryloxypropyltrimethoxysilane is 100:3.5; the mass ratio of silane-modified silicon oxide to nano-cerium oxide is 100:11; the mass ratio of platinum to vinyl silicone oil in the slow-release catalyst is 0.6:10000; the mass ratio of hydrogen-containing silicone oil to vinyl silicone oil is 16:100, and the hydrogen content of the hydrogen-containing silicone oil used is 0.4%.
[0183] In this embodiment, the mass ratio of hydrogen-containing silicone oil to vinyl silicone oil was increased from 15:100 in Example 2 to 16:100, while the hydrogen content of the hydrogen-containing silicone oil was decreased from 0.5% in Example 2 to 0.4%, so that the total amount of active hydrogen in the system remained basically consistent with that in Example 2. This eliminated the interference of changes in the total amount of crosslinking agent on the results and ensured that the performance difference mainly stemmed from changes in the amount of coupling agent, the proportion of heat-resistant additives, and the amount of platinum catalyst.
[0184] Example 5
[0185] A high-strength heat-resistant silicone rubber composite material is prepared in a manner that is basically the same as that in Example 1, except that the pore size of the first carrier is 10 nm and the pore size of the second carrier is 5 nm; the mass ratio of the first slow-release catalyst to the second slow-release catalyst is 50:50.
[0186] Example 6
[0187] A high-strength heat-resistant silicone rubber composite material is prepared in a manner that is basically the same as that in Example 1, except that only the first slow-release catalyst is present in the slow-release catalyst.
[0188] Example 7
[0189] A high-strength heat-resistant silicone rubber composite material is prepared in a manner that is basically the same as that in Example 1, except that in the heating and cooling cycle, the first heating rate is 10℃ / min, the first cooling rate is 5℃ / min, the second heating rate is 10℃ / min, the second cooling rate is 5℃ / min, and the third heating rate is 10℃ / min.
[0190] Example 8
[0191] A high-strength heat-resistant silicone rubber composite material is prepared in a manner that is basically the same as that in Example 1. The difference is that, in the heating and cooling cycle, only the first heating rate is adjusted to 4℃ / min and the first cooling rate is 2℃ / min, while the second heating rate, the second cooling rate and the third heating rate remain unchanged.
[0192] Example 9
[0193] A high-strength heat-resistant silicone rubber composite material is prepared in a manner that is basically the same as that in Example 1. The difference is that, in the heating and cooling cycle, only the second heating rate is adjusted to 4℃ / min and the second cooling rate is 2℃ / min, while the second heating rate, the second cooling rate and the third heating rate remain unchanged.
[0194] Example 10
[0195] A high-strength heat-resistant silicone rubber composite material is prepared in a manner that is basically the same as that in Example 1, except that the silane coupling agent used is γ-glycidyl etheroxypropyltrimethoxysilane.
[0196] Example 11
[0197] A high-strength heat-resistant silicone rubber composite material is prepared in a manner that is basically the same as that in Example 1, except that the silane coupling agent used is γ-aminopropyltriethoxysilane.
[0198] Example 12
[0199] A high-strength heat-resistant silicone rubber composite material is prepared in a manner that is basically the same as that in Example 1, except that the platinum catalyst used is a platinum-divinyltetramethyldisiloxane complex.
[0200] Example 13
[0201] A high-strength heat-resistant silicone rubber composite material is prepared in a manner that is basically the same as that in Example 1, except that the platinum catalyst used is a platinum-cyclohexene complex.
[0202] Example 14
[0203] A high-strength heat-resistant silicone rubber composite material is prepared using a method basically the same as that in Example 1, except that the rubber compound undergoes plasma surface treatment after oven treatment. The process is as follows:
[0204] The semi-finished product after oven treatment is placed in a low-temperature plasma treatment device, and the vacuum is evacuated to a working pressure of 60 Pa. The treatment gas (argon / oxygen mixture, mixing ratio Ar:O2=95:5) is introduced at a flow rate of 20 sccm. The radio frequency power supply is turned on, the discharge power is 100W (power density 1.5W / cm²), and the treatment time is 3 minutes. After the treatment, the gas is released and the sample is taken out. The treated sample should be coated or bonded within 4 hours to make full use of the surface active groups.
[0205] Example 15
[0206] A high-strength heat-resistant silicone rubber composite material is prepared in a manner that is basically the same as that in Example 5, except that the mass ratio of the first slow-release catalyst to the second slow-release catalyst is 40:60.
[0207] Example 16
[0208] A high-strength heat-resistant silicone rubber composite material is prepared in a manner that is basically the same as that in Example 5, except that the mass ratio of the first slow-release catalyst to the second slow-release catalyst is 60:40.
[0209] Example 17
[0210] A high-strength heat-resistant silicone rubber composite material is prepared in a manner that is basically the same as that in Example 15, except that the mass ratio of the first slow-release catalyst to the second slow-release catalyst is 30:70.
[0211] Example 18
[0212] A high-strength heat-resistant silicone rubber composite material is prepared in a manner that is basically the same as that in Example 15, except that the mass ratio of the first slow-release catalyst to the second slow-release catalyst is 70:30.
[0213] Comparative Example 1
[0214] A silicone rubber material is prepared in a manner that is basically the same as in Example 1, except that unmodified silicon oxide is used instead of silane-modified silicon oxide.
[0215] Comparative Example 2
[0216] A silicone rubber material is prepared in a manner that is basically the same as in Example 1, except that nano-cerium oxide is not added.
[0217] Comparative Example 3
[0218] A silicone rubber material is prepared in a manner that is basically the same as in Example 1, except that platinum chlorate is used instead of the slow-release catalyst.
[0219] Comparative Example 4
[0220] A silicone rubber material is prepared in a manner that is basically the same as that in Example 1, except that the secondary crosslinking does not use a heating and cooling cycle, but directly heats the pre-crosslinked rubber material to 130°C and holds it at that temperature for 1 hour.
[0221] The materials prepared in the above embodiments and comparative examples were subjected to the following performance tests:
[0222] Tensile strength: Tested according to GB / T 528-2009;
[0223] Tear strength: Tested according to GB / T 529-2008;
[0224] Hardness: Tested according to GB / T 531.1-2008;
[0225] Heat resistance aging performance: The sample was placed in a 300℃ high temperature aging test chamber for 72 hours, and then its tensile strength was tested and the tensile strength retention rate was calculated.
[0226] The test results are detailed in Table 1:
[0227] Table 1
[0228]
[0229] As shown in Table 1, the silicone rubber composite material prepared by the preparation method provided in this application has excellent mechanical properties and heat resistance. After heat aging treatment, the tensile strength retention rate is greater than 70%, which is better than the silicone rubber materials of comparative examples 1-4.
[0230] Compared with Examples 3-4, the materials obtained in Examples 1-2 have higher mechanical properties and higher retention of tensile strength after aging. This may be because the mass ratio of each raw material used is within the preferred range, resulting in a stronger degree of cross-linking.
[0231] Compared with Example 5, the mechanical properties and tensile strength retention rate of the material obtained in Example 1 are slightly higher. It can be seen that the increased pore size of the first and second supports increases the release rate of the platinum catalyst, but it is still within a controllable range, and good mechanical properties and heat resistance can still be obtained.
[0232] Compared to Example 6, the material obtained in Example 1 exhibits slightly higher mechanical properties and tensile strength retention. This indicates that the sustained-release effect of the platinum catalyst in a single-pore size controlled-release catalyst is not as good as the graded sustained-release effect achieved by a dual-pore size distribution.
[0233] Compared with Examples 8-9, the material obtained in Example 1 exhibits higher mechanical properties and tensile strength retention. This indicates that during the heating and cooling cycle, when the first heating rate or the second heating rate is greater than or equal to 5°C / min, and the first cooling rate or the second cooling rate is greater than or equal to 3°C / min, the crosslinking reaction exhibits better uniformity, thereby resulting in stronger mechanical properties and heat aging resistance of the obtained material.
[0234] The results of Comparative Examples 1-4 show that failure to modify silica with silane, failure to add heat-resistant additives, failure to use slow-release catalysts, or failure to perform heating and cooling cycles will all reduce the mechanical properties and heat aging resistance of the resulting silicone rubber materials.
[0235] Finally, it should be noted that other embodiments of the invention will readily occur to those skilled in the art upon consideration of the specification and practice of the invention disclosed herein. This invention is intended to cover any variations, uses, or adaptations of the invention that follow the general principles of the invention and include common knowledge or customary techniques in the art not disclosed herein, and various modifications and changes may be made without departing from its scope. The scope of the invention is limited only by the appended claims.
Claims
1. A method for preparing a high-strength, heat-resistant silicone rubber composite material, characterized in that, include: Silane-modified silica was mixed with a heat-resistant additive and dispersed in an organic solvent to obtain a filler premixed slurry; Platinum catalysts are supported on a support to obtain slow-release catalysts; After mixing vinyl silicone oil with the filler premix slurry, the slow-release catalyst is added, and hydrogen-containing silicone oil is added under an inert atmosphere to carry out a pre-crosslinking reaction and a secondary crosslinking reaction to obtain a rubber compound; wherein, the secondary crosslinking reaction includes several heating and cooling cycles; The rubber compound is post-processed to obtain the high-strength heat-resistant silicone rubber composite material.
2. The preparation method according to claim 1, characterized in that, The silane-modified silicon oxide is prepared by a method comprising the following steps: Silica and silane coupling agent are mixed at a mass ratio of 100:(1-3) and stirred at 50℃-60℃ for 10min-20min to obtain the silane-modified silica. And / or, the mixing and dispersion of silane-modified silica with a heat-resistant additive in an organic solvent includes: The silane-modified silica and the heat-resistant additive are mixed at a mass ratio of 100:(5-10), stirred at 70℃-80℃ for 15min-30min, and then an organic solvent is added and ultrasonically dispersed for 10min-30min to obtain the filler premix slurry.
3. The preparation method according to claim 2, characterized in that, The silane coupling agent includes at least one of γ-methacryloxypropyltrimethoxysilane, γ-glycidyl etheroxypropyltrimethoxysilane, and γ-aminopropyltriethoxysilane. And / or, the heat-resistant additive includes at least one of cerium oxide, titanium oxide, and cerium hydroxide; And / or, the organic solvent includes at least one of anhydrous isopropanol and n-butanol; And / or, the mass ratio of the silicon dioxide to the organic solvent is 10:(5-8).
4. The preparation method according to claim 1, characterized in that, The carrier includes a first carrier and a second carrier, wherein the pore size of the first carrier is greater than or equal to the pore size of the second carrier; The slow-release catalyst includes a first slow-release catalyst and a second slow-release catalyst.
5. The preparation method according to claim 4, characterized in that, The process of loading the platinum catalyst onto the support includes: The platinum catalyst was dispersed in an alcohol solvent to obtain a platinum catalyst dispersion. According to the mass ratio of the platinum catalyst to the first support being (1-5):100, the first support is added to the platinum catalyst dispersion and impregnated for 12h-24h, with regular stirring during the period, and then filtered and dried to obtain the first slow-release catalyst. The second support was added to the platinum catalyst dispersion at a mass ratio of (1-5):100, and impregnated for 12-24 hours with periodic stirring. The mixture was then filtered and dried to obtain the second slow-release catalyst.
6. The preparation method according to claim 4, characterized in that, The pore size of the first carrier is 2nm-10nm; And / or, the pore size of the second carrier is 2nm-5nm; And / or, the mass ratio of the first sustained-release catalyst to the second sustained-release catalyst is (4-6):(4-6).
7. The preparation method according to claim 4, characterized in that, The platinum catalyst includes at least one of chloroplatinic acid, platinum-divinyltetramethyldisiloxane complex, and platinum-cyclohexene complex; And / or, the first carrier includes at least one of mesoporous silica, mesoporous alumina, mesoporous silica-alumina composite, and molecular sieve; And / or, the second carrier includes at least one of activated carbon and mesoporous silica.
8. The preparation method according to claim 1, characterized in that, The mass ratio of the vinyl silicone oil to the filler premixed slurry is 10:(2-4). And / or, the temperature of the mixing system is 40℃-50℃; And / or, the mass ratio of platinum in the slow-release catalyst to the vinyl silicone oil is (0.05-0.2):10000; And / or, the flow rate of the inert atmosphere is 0.5 L / min to 2 L / min; And / or, the hydrogen content of the hydrogen-containing silicone oil is 0.5%-1.2%; And / or, the mass ratio of the hydrogen-containing silicone oil to the vinyl silicone oil is (5-15):
100.
9. The preparation method according to claim 1, characterized in that, The heating and cooling cycle includes: Heat to 130℃-140℃ at a first heating rate of 5℃ / min or higher and hold for 5min-10min. Then, cool down to 100℃-110℃ at a first cooling rate of 3℃ / min or higher and hold for 5min-10min. Then, increase the temperature to 150℃-160℃ at a second heating rate of 5℃ / min and hold for 10min-15min. Then, cool down to 120℃-130℃ at a second cooling rate of 3℃ / min or higher and hold for 5min-10min. Then, increase the temperature to 160℃-170℃ at a third heating rate of 5℃ / min and hold for 15min-20min. And / or, the number of times is 2 to 3 times.
10. The preparation method according to claim 1, characterized in that, The post-processing includes constant temperature and humidity treatment, silicone oil bath treatment, and oven treatment.
11. The preparation method according to claim 10, characterized in that, The temperature of the constant temperature and humidity treatment is 23℃-27℃, the relative humidity of the constant temperature and humidity treatment is 60%-70%, and the time of the constant temperature and humidity treatment is 12h-24h. And / or, the silicone oil treatment includes: placing the adhesive in silicone oil with a viscosity of 100 mPa•s-500 mPa•s and treating it at 80℃-100℃ for 1h-2h; And / or, the temperature of the oven is 100℃-120℃, and the time of the oven treatment is 30min-60min.
12. The preparation method according to claim 11, characterized in that, The silicone oil includes methyl silicone oil, phenyl silicone oil, or ethyl silicone oil.
13. The preparation method according to claim 1, characterized in that, Following the post-processing, plasma surface treatment is also included.
14. A high-strength heat-resistant silicone rubber composite material, prepared by the preparation method according to any one of claims 1-13.
15. A spacer bar for electrical fittings, characterized in that, Including the high-strength heat-resistant silicone rubber composite material as described in claim 14.
Citation Information
Patent Citations
Heat-resistant silicone rubber and preparation method thereof
CN104046039A